2006
DOI: 10.1007/s00134-006-0126-5
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles to organ donation in Swedish intensive care units

Abstract: The identified obstacles (neutral approach of donation request, ethical problems concerning the potential donor and the relatives, varying competence in diagnosing total brain infarction, and lack of intensive care bed resources) require tailored efforts in order to increase organ donation. Checking these factors can be used as a quality control when analysing donation activities at hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 16 publications
0
29
0
1
Order By: Relevance
“…Failures to exploit the potential for organ and tissue donation have been attributed to a number of factors, amongst them being the fact that health care professionals and CC staff in particular have recurrent problems with recognizing a patient as a potential donor, approaching families of medically suitable donors and obtaining consent for donation [11–14].…”
Section: Discussionmentioning
confidence: 99%
“…Failures to exploit the potential for organ and tissue donation have been attributed to a number of factors, amongst them being the fact that health care professionals and CC staff in particular have recurrent problems with recognizing a patient as a potential donor, approaching families of medically suitable donors and obtaining consent for donation [11–14].…”
Section: Discussionmentioning
confidence: 99%
“…There can be psychosocial, organizational and professional barriers to organ donation. Studies show that the staff's level of knowledge and experience influence their confidence in discussions and briefings on organ donation both with their own colleagues and also with relatives/power of attorney for the patient [3,[11][12][13][14][15]. The nurses' requirements for knowledge and understanding of the process of organ donation, definitions of death and various changes that occur in relation to the death processes, as well as the needs of next of kin, have been documented in several studies [5,11,[16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…How to approach the question of organ donation and attitudes towards work with potential donors were discovered as obstacles to organ donation, in a study among Swedish physicians. Sanner suggests that the hospitals should give a higher priority for the organ donation process and that a proactive donor detection programme could be a key to success [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The doctors' knowledge about organ donation, attitude to it and ability to relate to the potential organ donor and his or her next of kin may be decisive for obtaining consent to an organ donation (2)(3)(4)(5)(6)(7). A review article published in 2009 (5) showed that specific skills in the person who provides information and inquires, as well as the timing of the inquiry, may have a greater effect on the likelihood that the next of kin will provide consent for an organ donation than legislation and regulations.…”
mentioning
confidence: 99%